Natural Disaster Preparedness in Small and Medium Industries in Palu Bay Area : 5 Years After the Disaster) Earthquake, Tsunami and Liquefaction - Mohamad Adfar (International Forum of Researchers and Lecturers, 2025)
Palu Bay is located in Central Sulawesi Province and is one of the active seismic bays in Indonesia which is crossed by the Palu-Koro fault segmentation. On September 28, 2018, an earthquake disaster occurred in this area accompanied by a tsunami and liquefaction. Palu City, Sigi Regency and Donggala Regency are areas that are severely affected by this disaster. Research in this region is to determine the level of preparedness of Small and Medium Industries in facing natural disasters in the future. The population of SMEs is 745 businesses/people with a probability sampling technique, namely Proportional Random Sampling. The assessment was carried out through a questionnaire involving 260 SME samples randomly selected in the three regions. The results of the study illustrate that the total preparedness of SMEs in the Palu Bay Area in facing natural disasters is 34.9% of respondents stated as